2021
DOI: 10.3390/scipharm89040050
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry and Evidence-Based Traditional Uses of the Genus Achillea L.: An Update (2011–2021)

Abstract: Knowledge within the field of phytochemistry research has accelerated at a tremendous speed. The excess of literature reports featuring plants of high ethnopharmacological importance, in combination with our interest in the Asteraceae family and traditional medicine, led us to acknowledge the value of the Achillea L. genus. In a broad context, the various Achillea species are used around the globe for the prevention and treatment of different diseases, including gastrointestinal problems, haemorrhages, pneumon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 106 publications
0
21
0
Order By: Relevance
“…Achillea millefolium L. (yarrow) is a flowering plant traditionally used in the treatment of digestive and hepatobiliary disorders, inflammation, and diabetes [ 1 ]. Recent reports indicated that Achillea genus presented important biological activities, such as antioxidant, anti-inflammatory and antitumor activities [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Achillea millefolium L. (yarrow) is a flowering plant traditionally used in the treatment of digestive and hepatobiliary disorders, inflammation, and diabetes [ 1 ]. Recent reports indicated that Achillea genus presented important biological activities, such as antioxidant, anti-inflammatory and antitumor activities [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the widely known benefits of this plant, the study of its composition and biological properties has awakened a constant interest in developing pharmaceutical, nutraceutical, and food products [ 14 , 15 , 16 ]. Dried and fresh upper parts from yarrow have been used to prepare aqueous and alcoholic extracts for the treatment of several health problems, such as diabetes and cardiovascular, respiratory, hepatobiliary, spasmodic, and gastrointestinal disorders [ 17 ]. In addition, yarrow has been used externally for the treatment of skin and mucous membrane inflammation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The estimation was made for different kinds of molecules such as flavonoids, tannins, phenolics, saponins, and alkaloids, which are present in varying concentrations in the hydro-alcoholic extract, as shown in Figure 1. Specifically known phytochemicals (Table 1) present in this plant include sesquiterpene lactone, Achillolide A, 3,5,4'trihydroxy-6,7,3'-trimethoxyflavone, cirsiliol, cirsimaritin, and a number of hydrocarbon compounds which have been reported to possess pharmacological properties including anticancer effects (Barda et al, 2021;Bartolotti et al, 2018;Patocka and Navratilova, 2019). Studies have shown that various secondary metabolites of plant origin have the ability to inhibit the process of carcinogenesis in preclinical and clinical models (Ullah et al, 2014).…”
Section: Extract Of a Fragrantissima Evince The Presence Of Structura...mentioning
confidence: 99%